DEN - Stichting DEN (2008)
[Dt.:] Das Digitaal Erfgoed Nederland (DEN) unterstützt die Digitalisierung des Kulturerbes in den Niederlanden in Hinblick von Informations- und Kommunikationstechnologie (IKT). DEN informiert über seine Website über Dienstleistungen und Projekte (eigene Datenbank). - [Engl.:] Digitaal Erfgoed Nederland (DEN) - or Digital Heritage Netherlands - is the Dutch national knowledge institute for ICT and cultural heritage. Commissioned by the Dutch Ministry of Education, Cultural Affairs and Science, DEN collects and distributes knowledge about ICT standards and practices in order to improve the quality of digitisation and digital services. This way, DEN supports the cultural heritage sector to build a national Digital Heritage Collection in a professional, future-proof, and public-oriented manner. The website informs about DEN its services and goals. Beside this it offer a searchable project database.